[Rezension von: Drevon, Jerome, Institutionalizing Violence: Strategies of Jihad in Egypt] - Sinai, Joshua (Perspectives on terrorism, 2024)
So many books are published on terrorism- and counter-terrorism-related subjects that it is difficult to catch up on a large backlog of monographs and volumes received for review. In order to deal with this backlog, this column consists of capsule reviews of nine books.